Design and implementation of a three-phase dual active bridge DC-DC converter for MVDC applications - Lee, Youngsil (2019)
This thesis investigates the design considerations of a bidirectional and isolated 3DAB converter with a medium voltage side (ranging up to 40 kV DC), a low voltage side (1.1 kV and 5.2 kV DC), and a rated power of 4 MW. This thesis shows that the above design considerations should be taken into account for passive devices. First, the use of a snubber capacitor in medium voltage and medium frequency operating condition is proposed. Secondly, this thesis presents a step-by-step design and optimisation for medium frequency transformer. The work starts with an overview of the operation of the 3DAB converter topology, followed by a systematic investigation of the design considerations for the given 3DAB converter.